2011
DOI: 10.1037/a0020859
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive complaints and longitudinal changes in memory and brain function.

Abstract: Objective Subjective cognitive complaints are often used in the diagnosis of memory and other cognitive impairment. This study examined whether cognitive complaints are associated with longitudinal changes in cognition and cross-sectional differences in regional brain function during memory performance in 98 participants with a mean age of 75. Method The Cognitive Failures Questionnaire (CFQ) assessed cognitive complaints and mixed effects regression models were used to determine whether mean CFQ scores pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 45 publications
9
135
2
Order By: Relevance
“…Age-related cognitive decline is widely acknowledged as a relatively common phenomenon (Hanninen et al, 1996), but a longitudinal study found that higher failures predicted a steeper-than-usual trajectory of decline in verbal memory function in particular (Hohman et al, 2011). Despite this, there were few differences between the overall number of everyday failures reported by older and younger people (Kramer, Humphrey, Larish, Logan, & Strayer, 1994;Lange & Süß, 2014;Reese & Cherry, 2006), and one study found that older people actually reported fewer slips (Mecacci & Righi, 2006).…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…Age-related cognitive decline is widely acknowledged as a relatively common phenomenon (Hanninen et al, 1996), but a longitudinal study found that higher failures predicted a steeper-than-usual trajectory of decline in verbal memory function in particular (Hohman et al, 2011). Despite this, there were few differences between the overall number of everyday failures reported by older and younger people (Kramer, Humphrey, Larish, Logan, & Strayer, 1994;Lange & Süß, 2014;Reese & Cherry, 2006), and one study found that older people actually reported fewer slips (Mecacci & Righi, 2006).…”
Section: Agementioning
confidence: 99%
“…Even healthy ageing appears to be associated with decline in specific types of cognitive functions, such as those involving the demand for recall (Hohman, Beason-Held, Lamar, & Resnick, 2011;Rast, Zimprich, Van Boxtel, & Jolles, 2009). However, increased awareness of dementia means middle-aged and older people are experiencing more anxiety about normal cognitive decline, a phenomenon known as 'dementia worry' (Kessler, Bowen, Baer, Froelich, & Wahl, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The standardized application of tests to elderly individuals with cognitive complaints is a manner of rendering the concept of cognitive impairment both valid and reliable. 38 …”
Section: Figurementioning
confidence: 99%
“…Most of these studies on the relation between cognitive complaints and cognitive functioning have been made on elderly [20,21,22,23,24,25,26,27,28,29,30,31], while population studies on non-elderly adults are few with mixed results [32,33,34,35,36]. This in addition to methodological issues regarding measures of cognitive functioning in these studies make it difficult to draw any clear conclusions.…”
Section: Introductionmentioning
confidence: 99%